Molecular and epigenetic responses to crowding stress in rainbow trout (Oncorhynchus mykiss) skeletal muscle - Aravena-Canales, Daniela; Valenzuela-Muñoz, Valentina; Gallardo-Escarate, Cristian; Molina, Alfredo; Valdés, Juan Antonio (Frontiers in Endocrinology, 2025)
BackgroundChronic stress is a critical challenge in fish aquaculture, adversely affecting growth, health, and overall productivity. Among the most significant chronic stressors in intensive farming is crowding, which triggers the release of cortisol, the primary stress hormone in fish. Cortisol re-allocates energy away from growth-related processes toward stress response mechanisms. Consequently, overcrowded fish often exhibit slower growth rates, and impaired skeletal muscle development. Understanding the mechanisms underlying crowding stress and their long-term effects, including epigenetic changes, is essential for optimizing farming conditions, and enhancing fish welfare.ObjectiveThis study aims to characterize the physiological, transcriptomic, and epigenomic responses in juvenile rainbow trout (Oncorhynchus mykiss) exposed for 30 days to high stocking densities.ResultsCrowding stress led to decreased weight in the high-density (HD) group. It also resulted in elevated cortisol levels, oxidative DNA damage, and protein carbonylation in skeletal muscle. Using RNA-seq, we identified 4,050 differentially expressed genes (DEGs), and through whole-genome bisulfite sequencing (WGBS), we detected 11,672 differentially methylated genes (DMGs). Integrative analyses revealed 263 genes with a negative correlation between upregulated expression and downregulated methylation, primarily associated with autophagy, mitophagy, and the insulin signaling pathway. Conversely, 299 genes exhibited the reverse trend, mainly linked to ATP-dependent chromatin remodeling.ConclusionThis study offers the first detailed exploration of the molecular responses in skeletal muscle to crowding stress, integrating RNA-seq and WGBS analysis in rainbow trout, offering valuable information for improving aquaculture practices.